Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $E(n)$ denote an nth root of unity. (For convenience, we may take $E(n) = \exp(\frac{2πi}{n})$.)

Prove that for any prime $p$ and any natural number $r$, we have $$ \prod_{\substack{j\\ \gcd(p^r, j) = 1}} \left(1 – E(p^r)^j\right) = p,$$ without using the formula to get the cyclotomic polynomial of $p^r$.

share|cite|improve this question
Without using what formula? And why without using it? – Phira Nov 11 '12 at 10:49
@Phira, because with using the formula it would be really direct. I wanted to see a proof without using the formula. The formula is Phi(x) = sum i= 1 to p-1 ( x^(i*p^(k-1))) – John Chang Nov 11 '12 at 13:20
It should be $\displaystyle{\prod_{\left(p^r,j\right)=1} \left(1 – E\left(p^r\right)^j\right) = p^r}$. – P.. Nov 12 '12 at 11:57
@Pambos, the cyclotomic polynomial of p^r, Phi(x) = sum i= 1 to p-1 ( x^(i*p^(k-1))) gives us that it is indeed p. I think. But I wanted to see a more detailed proof without using this formula. – John Chang Nov 12 '12 at 12:00
up vote 0 down vote accepted

Let $n$ be a natural number and let $E_n=e^{2\pi i/n}$. Then the polynomial $x^n - 1$ splits in $\mathbb{Q}(E_n)$ as

$x^n - 1 = (x - 1)(x - E_n)\cdots(x-E_n^{n-1})$, which yields:

$1+x+\cdots+x^{n-1} = \frac{x^n-1}{x-1} = (x - E_n)(x - E_n^2)\cdots(x-E_n^{n-1})$

and so we get the following result.

$\prod_{j=1}^{n-1}(1-E_n^j) = n$

Now let $n = p^m$, for some natural number $m$. Thus,

$p^m = \prod_{j=1}^{p^m-1}(1-E_{p^m}^j) = \prod_{(j, p^m)=1}(1-E_{p^m}^j)\prod_{(j, p^{m-1})=1}(1-E_{p^{m-1}}^j)\cdots\prod_{(j, p)=1}(1-E_p^j)$

Now look at the right side of the last equation. Each product $\prod_{(j, p^r)=1}(1-E_{p}^j)$ is greater than 1, and there are a total of $m$ factors of this form. Since the product of these $m$ factors is $p^m$, then each factor must be equal to $p$.

Therefore, $\prod_{(j, p^r)=1}(1-E_{p^r}^j) = p$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.